ANALYSIS COMMUNITY SATISFACTION ON HUNGAYONAA VILLAGE DEVELOPMENT PERFORMANCE, TILAMUTA DISTRICT, BOALEMO REGENCY - Frengki Razak; Ikram Muhammad; Aryati Hamzah (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The aim of this study was to determine the level of community satisfaction in village development performance in the Village Government of Hungayonaa, Tilamuta District, Boalemo Regency. The research method used in this research is a quantitative approach with this type of research using a survey. The study population was 1,066 families from 5 hamlets and the sample in the study was 87 people. The sampling technique used in this study is a non-probability sampling technique of purposive sampling. The data collection technique used in this study was a questionnaire or questionnaire and documentation. The data analysis technique used in this research is descriptive data analysis using a quantitative research approach. The results showed that the level of community satisfaction with the development performance of Hungayonaa Village, Tilamuta District, Boalemo Regency was still low, where the community's perception of village development performance was lower, namely 73.95% compared to community expectations, namely 80.48%. Of the two aspects of development assessed, the human aspect is lower than the physical aspect, namely 67.68% of human development performance. Meanwhile, the performance of physical development was 80.33%. This means that physical development is more dominant than human development.